Effects of caffeine, tea polyphenol and daidzein on the pharmacokinetics of lansoprazole and its metabolites in rats - Tao Wu; Ji Wu; Ping Gao; Daochun Xiang; Dong Liu; Hongping Song (Universidade de São Paulo, 2015)
abstract The aim of this study was to evaluate the effects of caffeine, tea polyphenol and daidzein on the pharmacokinetics of lansoprazole and its metabolites. Rats were intragastrically administered caffeine (30 mg·kg-1, once per day), tea polyphenol (400 mg·kg-1, once per day) or daidzein (13.5 mg·kg-1, once per day) for 14 days, followed by an intragastric administration of lansoprazole (8 mg·kg-1) on the 15th day. The plasma concentrations of lansoprazole and its two primary metabolites, 5-hydroxylansoprazole and lansoprazole sulfone, were determined by high-performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS). Tea polyphenol significantly elevated the Area Under the Curve (AUC) of lansoprazole from 680.29 ± 285.99 to 949.76 ± 155.18 μg/L.h and reduced that of lansoprazole sulfone from 268.82 ± 82.37 to 177.72 ± 29.73 μg/L.h. Daidzein increased the AUC of lansoprazole from 680.29 ± 285.99 to 1130.44 ± 97.6 μg/L.h and decreased that of lansoprazole sulfone from 268.82 ± 82.37 to 116.23 ± 40.14 μg/L.h. The pharmacokinetics of 5-hydroxylansoprazole remained intact in the presence of tea polyphenol or daidzein. Caffeine did not affect the pharmacokinetics of lansoprazole and its metabolites. The results imply that tea polyphenol and daidzein may inhibit the in vivo metabolism of lansoprazole by suppressing CYP3A.